INNOVATIVE TECHNOLOGIES FOR TEACHING FOREIGN LANGUAGES - Abduvaliyeva , Farangizxon ("Science Shine" International scientific journal, 2024)
The project approach of teaching foreign languages at universities is the subject of this essay. The project approach is defined in the article as a specifically planned, motivated learning exercise with the goal of investigating and resolving a theoretically or practically important issue. The article outlines the major phases of project activity as well as the typology of projects. The primary duties involved in carrying out project activities at the institution are also taken into account. Currently, there are several benefits to employing the project method in pedagogy over more conventional teaching approaches. Students' capacity to think constructively, their enthusiasm to study, their teamwork skills, their leadership abilities, their collaboration and self-presentation abilities—all of which are developed by working on projects.